HOW FAR FISCAL DOMINANCE MATTERS FOR A DEVELOPING ECONOMY - S. Shvets (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The growing public debt that intensifies with a frequency of economic crises grasps a high rating in the current economic debates. There is an urgent need for implementing an effective policy regime targeted at handling the public debt problem. The fiscal dominance policy, usually practiced to ensure strong recovery and growth, has a strict guideline for identifying a degree of fiscal expansion and monetary accommodation. Given a dilemma between growth and debt burden, the government should mobilize the most effective policy instrument targeted at the highest fiscal multiplier and does not cross a debt-to-GDP threshold ratio. Following an effective practice of fiscal management, this instrument is associated with public investment. The paper aims to assess the magnitude of the public investment multiplier by following a stable growth path limited by a prescribed debt limitation for a developing economy. To achieve the goal, we use an elaborated New Keynesian model, which besides an active fiscal and monetary stances, also includes a high share of non-Ricardian households, the separability in preferences between private and government consumption, a low level of public investment efficiency, and the substantiated degree of nominal and real rigidities. The obtained present value cumulative output multiplier for public investment grasps the point 2.0 in maximum over two years of the impulse response function. The multiplier effect proves to be high enough to offset temporary public debt growth and maintain a sustainable growth path over the long run. The verified measure of fiscal dominance contradicts an active monetary stance and, among other things, has to be counterbalanced by an appropriate efficiency and productivity of public investment and degree of price stickiness.